Genitourinary Cancers (Cancer Treatment and Research,, 2018)
This book addresses the most pressing current questions in the management of urologic malignancies. The rapid advances in imaging and molecular markers are placed into a clinical context, with explanation of their effects on prognosis and treatment planning. Similarly, progress in immunotherapy is carefully examined, focusing in particular on the role of immune checkpoint inhibitors in both early- and late-stage urologic malignancies. Looking beyond the improvements in minimally invasive techniques for urologic cancers, the impacts of care coordination pathways and enhanced recovery after surgery protocols are reviewed. Readers will also find enlightening discussion of the decision algorithm for the treatment of early-stage, high-grade bladder cancer, taking into account evidence on the most advanced treatment options and the circumstances in which surgery may need to be expedited. The penultimate chapter discusses the Cancer Genome Atlas project for bladder cancer, and the book closes by considering contemporary medical and surgical management of testicular cancer.